Safety and efficacy of high-dose cyclophosphamide, etoposide and ranimustine regimen followed by autologous peripheral blood stem cell transplant for patients with diffuse large B-cell lymphoma. Issue 11 (November 2014) - Kobayashi, Yujin; Hatta, Yoshihiro; Sugitani, Masahiko; Hojo, Atsuko; Nakagawa, Masaru; Kusuda, Machiko; Uchino, Yoshihito; Takahashi, Hiromichi; Kiso, Satomi; Hirabayashi, Yukio; Yagi, Mai; Kodaira, Hitomi; et al.
Abstract: We retrospectively evaluated the safety and efficacy of high-dose chemotherapy consisting of cyclophosphamide, etoposide and ranimustine (CEM) with autologous peripheral blood stem cell transplant (PBSCT) in 55 adult patients with relapsed or high-risk de novo diffuse large B-cell lymphoma (DLBCL) or DLBCL associated with follicular lymphoma. This included 36 patients in the upfront setting in their first complete remission. The median follow-up of 42 patients surviving at the time of the analysis was 52 months (range 1–159). Relapse or disease progression after PBSCT was a frequent cause of death, but no therapy-related mortality associated with PBSCT was observed. The 5-year overall survival and progression-free survival were 70.6% (95% confidence interval [CI], 54.0–82.1) and 57.0% (95% CI, 39.5–71.2), respectively. Chronic renal impairment, therapy-related myelodysplastic syndrome and prostate cancer were the major late complications. The CEM regimen is a tolerable, effective conditioning regimen for autologous PBSCT for DLBCL, with no therapy-related mortality observed.